The Positive And Negative Effects Of Digital Culture On Undergraduate Students Of Library Departments And Information In The Arab World From Their Point Of View And Their Attitudes Towards It (Journal of Namibian Studies : History Politics Culture, 2024)
This study aimed to identify the positive and negative effects of digital culture on undergraduate students. The first for libraries and information departments in the Arab world from their point of view and their attitudes towards it. The study population consisted of a random sample of 650 people, of whom (633) answered, at a rate of (97.4%), The Arab world was divided into three regions: (the countries of the Levant, the Arab Gulf countries, and the Arab countries in Morocco Arabia and Africa). The researcher designed a questionnaire whose validity and reliability were verified as a study tool to collect information. It consisted of two main areas - the first: the positive effects, and the second: the negative effects. The researcher divided each field into three sub-fields -personal domain, social domain and academic domain). To achieve the goal of the study. The researcher relied on the descriptive survey method. The results showed that the positive personal and academic effects of  digital culture has a high rating level, while social impact has a medium rating level and that. Negative effects for all domains (personal, social and academic) respectively have also received degrees of average estimate, (between the arithmetic averages (α≤0.05). The results also showed that there were no statistically significant differences when indicating. To estimate the effects of digital culture by students of library departments on them due to the variables (gender, academic level, and region), their attitude towards digital culture was positive and high.